(untitled) (EAAE Annual Conference Proceedings, 2016)
EAAE schools presented their approach to architectural education and institutional profile with a poster. This opened up opportunity for mutual discussion and inspiration. As highlighted in several former EAAE conferences before, at present, schools around Europe are updating and innovating their program to prepare the next generation students for future professional practice.